Three-Year Changes in Low-Income Children's Physical Activity: Prospective Influence of Neighborhood Environment and Parent Supportive Behavior - Simone A. French, PhD; Yingling Fan, PhD; Alicia S. Kunin-Batson, PhD; Jerica M. Berge, PhD, MPH, LMFT; Nidhi Kohli, PhD; Rik Z. Lamm, BS; Nancy E. Sherwood, PhD (Elsevier, 2021)
Objectives: To prospectively evaluate parent supportive behaviors (PSB) for child physical activity (PA) and neighborhood environment variables on changes in child PA over 3 years. Study design: Secondary data analysis of the Now Everybody Together for Amazing and Healthful Kids-Works study with 534 parent-child (age 2-4 years) dyads randomized to a community-based pediatric obesity prevention intervention for 3 years (92% retention). PSB and neighborhood environmental variables were examined in relation to changes in child moderate-to-vigorous PA (MVPA), light and sedentary activity, and screen time. Child and parent accelerometry data were collected at visit 0, 12, 24, and 36 months. Mixed multivariate models were used to examine independent and interactive effects of parent-level and neighborhood-level variables on changes in child PA outcomes. Results: PSB significantly interacted with visit on change in child MVPA (β = 0.12) and sedentary behaviors (β = -0.18). Over 3 years, a 1-unit increase in PSB was associated with an average increase of 4.3 minutes/day of MVPA and an average decrease of 6.5 minutes/day of sedentary time. Significant main effects were observed for PSB and 3-year change in child screen time (β = -0.05). The children of parents with higher PSB at baseline watched an average of 1.8 fewer minutes/day of screen time compared with parents with lower baseline PSB. Neighborhood-level variables were not significantly associated with changes in child PA outcomes. Conclusions: Parents who increase their supportive behaviors for their child's PA have children who are more physically active and less sedentary over time. Interventions to increase preschool-age children's PA may enhance their effectiveness by targeting parents' supportive behaviors for their child's PA.